Effect of diode laser combined with minocycline hydrochloride in nonsurgical periodontal therapy: a randomized clinical trial - Congchong Yang; Xikai Wang; Yanli Wang (BMC, 2022)
Abstract Background This study aimed to assess the effect of diode laser combined with minocycline hydrochloride in conventional nonsurgical periodontal therapy. Methods Ninety-two patients and 1206 teeth were included in this study. The patients were diagnosed moderate or severe periodontal diseases with the presence of teeth in at least 3 quadrants in the oral cavity. Each patient's quadrants were randomly divided into three treatment groups as following, Control group: scaling and root planning (SRP); Experimental group 1 (Exp 1): SRP + minocycline hydrochloride; Experimental group 2 (Exp 2): SRP + 809 nm diode laser + minocycline hydrochloride. The minocycline in Exp 1 and Exp 2 was applied once per week, for 4 weeks. Clinical examinations including periodontal probing depth (PD), clinical attachment level (CAL) and bleeding index (BI), and the secretion of inflammatory factor (tumor necrosis factor, TNF-α) was detected by ELISA before and 3, 6 months after the treatments. The differences among these groups were assessed by One-Way ANOVA and Kruskal-Wallis test. P-value < 0.05 was considered significant. Results All the periodontal indexes (PD, CAL and BI) were improved after each treatment and the secretion of TNF-α was reduced for all three groups. In patients with deep periodontal pockets, Exp 2 showed significant improvements in all indexes comparison with Con group and Exp group 1. Conclusions The synergistic effect of SRP and 809 nm diode laser combined with minocycline hydrochloride could play an efficient and reliable effect in the nonsurgical periodontal treatment approach. Trial registration The clinical trial was retrospectively registered in chictr.org.cn with registration ChiCTR2100051708 (01/10/2021).